(untitled) (Revista de Educação Pública, 2012)
Comparamos representações sociais (MOSCOVICI, 1961/1976) de pais e professores sobre ensino/aprendizagem. Os participantes foram pais (n= 49) e professores (n= 72) ligados a escolas públicas do ensino fundamental do Rio de Janeiro, através de questões abertas. Os grupos convergiram quanto ao que é aprender, mas diferiram sobre o ensinar. Constatamos diferenciação quanto às formas de avaliação de ensino e aprendizagem. Em ensino com os professores, se destacaram aspectos de planejamento, desenvolvimento intelectual/cultural, enquanto com os pais, aquisição de valores éticos/ morais. Para estes, contudo, houve mais referência a observar diferenças individuais, condições de trabalho e pesquisar. Teaching and learning according to parents and teachers from public schools in Rio de Janeiro - a social representations’ study Abstract We compared teachers’ and parents’ social representations (MOSCOVICI, 1961/1976) on teaching and learning. The participants included parents (P) (n=72) and teachers (T) (n=49) linked to primary public schools in Rio de Janeiro, throughout open questions. The groups agreed on what is learning, but they differed about teaching. Moreover, we verified differentiation regarding the diverse ways to evaluate teaching and learning. Among teaching activities with teachers stood out aspects of planning, and intellectual/cultural development, while with parents, acquisition of ethical/moral values. For the parents, however, there was more reference to aspects such as noticing individual differences, working conditions and researching. Keywords: Social representations. Teaching/ learning. Evaluation